Implementasi Pendekatan Pedagogik Kreatif Berbasis Model PJBL Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Elsa Syafila, Amanda; Hoiris Zuhro, Istihana; Maghfirli, Sabrina; Adinanda Siswoyo, Andika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Poetry writing is a key skill in Indonesian language learning that fosters students' imagination and expressive abilities. However, initial observations in Grade IV of SDN Demangan 1 revealed that students had difficulties in understanding poetic elements such as theme, rhyme, diction, and stanza structure. This study aims to improve students' poetry writing skills through the implementation of a creative pedagogy approach based on Project Based Learning (PjBL). The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles with 33 students as subjects. Data collection techniques included observation, interviews, and written tests, while data were analyzed through data reduction, data display, and conclusion drawing. The results showed a significant improvement in students' poetry writing abilities. The average class score increased from 70.75 in Cycle I to 83.3 in Cycle II, and the number of students achieving mastery rose from 19 to 27. Notable progress was also observed in aspects such as poetic structure and diction. These findings indicate that a creative pedagogy approach based on PjBL is effective in enhancing elementary students' poetry writing skills.